The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12917-019-2045-z
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography of the head in standing equids

Abstract: Background Computed tomography in standing horses has revolutionized diagnostic imaging. The O-arm®, a cone beam computed tomography (CBCT) scanner with a gantry opening of 96.5 cm is routinely used for image-guided spine and neurosurgery in humans. The aim of this study is to describe the set-up and first experiences using the O-arm® to achieve CBCT imaging of the head in standing horses. CT imaging of the predefined region of interest (ROI) was tested on 2 cadaveric heads, concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…The lower number of acquisitions can be explained by the smaller anatomy of extremities that usually can easily be covered by one acquisition of the fixed cylindrical volume. The extremities seem to be less affected by the respiratory swaying, which is not the case in the head and neck 8 …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The lower number of acquisitions can be explained by the smaller anatomy of extremities that usually can easily be covered by one acquisition of the fixed cylindrical volume. The extremities seem to be less affected by the respiratory swaying, which is not the case in the head and neck 8 …”
Section: Discussionmentioning
confidence: 81%
“…In comparison with standing CBCT of the head in standing sedated horses, the median number of acquisitions per region of interest is only one-half. 8 The lower number of acquisitions can be explained by the smaller anatomy of extremities that usually can easily be covered by one acquisition of the fixed cylindrical volume. The extremities seem to be less affected by the respiratory swaying, which is not the case in the head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in which multislice CT and cone beam CT were compared, however, Watanabe et al ( 39 ) showed that a smaller voxel size does not always improve spatial resolution as this may also depend on both the in-plane and longitudinal directed modulation-transfer function. Nevertheless, cone beam CT has not yet become area-wide established in equine dentistry due to various limitations, such as substantial sensitivity to motion artifacts, higher scatter, or a limited dimension of the field of view (FOV) ( 31 ). Additional artifacts of cone beam CT are alias artifacts by x-ray beam divergence and a higher noise level ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Domanska-Kruppa et al ( 15 ) just recently introduced conventional two-dimensional (2D) x-ray based cephalometry to investigate class II malocclusion and IIA using distinct cephalometric landmarks in Warmblood foals. Current advances of head CT in standing sedated horses ( 29 31 ) may allow for methodical standardization as well as single tooth measurements and will make 3D cephalometry clinically applicable.…”
Section: Introductionmentioning
confidence: 99%